Pengaruh Keluarga Terhadap Banyaknya Sampah Yang Ada Di Lingkungan Rt01 Banten Indah Permai Dengan Metode Regresi Linear Sederhana Menggunakan Orange Data Mining - Hasbi Assiddiq, Muhamad (Jejaring Penelitian dan Pengabdian Masyarakat (JPPM), 2024)
Waste is the accumulation of refuse generated by humans, which in the household context is categorized into organic, inorganic, and domestic waste. In the RT 01 RW 027 community of Perumahan Banten Indah Permai, each household produces waste daily, and these quantities are recorded by the neighborhood head to calculate the daily fee for waste collectors—where the tariff is based on the weight of waste (in kilograms) transported. By employing predictive methods and simple linear regression on the Orange platform, this study aims to measure the influence of family size on the daily volume of waste collected. The analysis results demonstrate a positive and significant relationship between family size, consumption patterns, and levels of environmental awareness with the rate of waste accumulation. These findings provide valuable insights for designing more effective waste management strategies, emphasizing the active role of each family in waste reduction and organization efforts.